ICU-Acquired Weakness: Diagnostic Yield of a Clinical Diagnosis with Additional Quantification of Myosin Loss in Adult Critically Ill Patients - Wouter Adema; Matthias Thomas Exl; Yvette Hedström; Lars Larsson; Joerg C. Schefold; Werner J. Z’Graggen (Journal of Clinical Medicine, 2026)
Background/Objectives: Intensive care unit acquired weakness (ICUAW) is common in critically ill patients. However, ICUAW is an umbrella term for multiple neuromuscular pathologies, including critical illness myopathy (CIM). This study aimed to evaluate the diagnostic yield of the clinical diagnosis of ICUAW compared with that of preferential myosin loss, i.e., the hallmark of CIM. Methods: Critically ill patients were enrolled within 24 h of intubation. Primary outcome was the frequency of ICUAW on day 10 after ICU admission, defined by a Medical Research Council (MRC) sum score of 1.5 at day 10 reached the MRC sum score threshold at day 17 compared to 21% with an M:A ratio ≤ 1.5. Patients with ICUAW had a higher six-month mortality rate (24%) than patients without (0%). Conclusions: Absence of ICUAW at day 10 after ICU admission was related with a favourable outcome. Myosin loss with an M:A ratio ≤ 1.5 was associated with a slower recovery of muscle function.